A lightweight key management framework for secure dynamic group based applications / Salman Iqbal Malik - Salman Iqbal , Malik (2017)
In recent years, group based applications have gained popularity due to their interesting and promising functionalities such as video on demand, teleconferencing and pay per view. The development of wireless networks and the emergence of mobile devices such as smartphones and tablets have also increased the demands for group based applications. These applications facilitate real-time information exchange among a large number of users over a wireless mobile environment. Due to the open nature of the wireless mobile environment, these applications are vulnerable to various kinds of security threats and thus, security is a major concern. Group Key Management Protocols (GKMPs) provide a secure way of communicating with group members across multiple entities. GKMPs provide member authentication, access control and management of the keying material. However, the implementation of GKMPs leads to significant computational, storage and communication overheads as well as potential system bottlenecks due to the high mobility of group members. Thus, the major issue that needs to be addressed in GKM is to minimize the computational, storage and communication overheads. The goal of this research is to address these issues and design a lightweight key management framework which requires fewer computations of keys for dynamic mobile users. A new group key management framework is proposed in this research, which is called the “DynaMic Group Key Management” (DM-GKM) framework. This framework exploits the advantages of an asymmetric key cryptosystem in order to guarantee security and it alleviates the rekeying overhead and distributing the independent Group Key (GK) for each cluster. Simulation and performance analysis demonstrate that the DM-GKM framework fulfils the requirements of a lightweight key management framework for large, dynamic groups of users. An analytical model, formal analysis and statistical analysis are also developed to determine the performance and security features of the proposed framework.